2016
DOI: 10.1095/biolreprod.115.131706
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Response of Human Trophoblastic Cells to Brucella abortus Infection and upon Interactions with Infected Phagocytes1

Abstract: Trophoblasts are targets of infection by Brucella spp. but their role in the pathophysiology of pregnancy complications of brucellosis is unknown. Here we show that Brucella abortus invades and replicates in the human trophoblastic cell line Swan-71 and that the intracellular survival of the bacterium depends on a functional virB operon. The infection elicited significant increments of interleukin 8 (IL8), monocyte chemotactic protein 1 (MCP-1), and IL6 secretion, but levels of IL1beta and tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
10
18
0
Order By: Relevance
“…canis infection with the secretion of IL-8 and RANTES, which attract neutrophils and monocytes to the infection site, and these phagocytes upon contact with the bacterium produce factors that further increase the inflammatory response of trophoblasts. Similar interactions between human trophoblasts and phagocytes in the context of Brucella abortus infection have been recently described by us [ 33 ].…”
Section: Discussionsupporting
confidence: 77%
“…canis infection with the secretion of IL-8 and RANTES, which attract neutrophils and monocytes to the infection site, and these phagocytes upon contact with the bacterium produce factors that further increase the inflammatory response of trophoblasts. Similar interactions between human trophoblasts and phagocytes in the context of Brucella abortus infection have been recently described by us [ 33 ].…”
Section: Discussionsupporting
confidence: 77%
“…Sw.71 is a well-characterized cell lineage that has been accepted as a study model for human trophoblast biology [54,57]. Studies have shown that Sw.71 secretes an array of cytokines when stimulated with different bacterial products [58,59]. In this study, major products secreted by Sw.71 upon contact with E. coli or the 2 Lactobacillus species were chemokines, a property of these trophoblast cells that has been previously reported [54,60].…”
Section: Resultssupporting
confidence: 61%
“…Infection of placental cells could alter this equilibrium by provoking a local inflammatory environment, contributing to pregnancy complications. In a recent report, Fernández, Ferrero, Hielpos, Fossati, and Baldi () observed increased IL‐6, IL‐8, and MCP‐1 secretion in the human cytotrophoblastic Swan‐71 cells infected with B . abortus .…”
Section: Discussionmentioning
confidence: 94%
“…Infection of placental cells could alter this equilibrium by provoking a local inflammatory environment, contributing to pregnancy complications. In a recent report, Fernández, Ferrero, Hielpos, Fossati, and Baldi (2016) This work is another step in understanding the physiopathology of Brucella infections in pregnant women. A plausible hypothesis is that bacteria would reach the placenta hidden inside maternal immune cells, known to be attracted to the implantation site and to infiltrate the maternal decidua during early pregnancy (Robbins & Bakardjiev, 2012).…”
Section: Consequences Of Brucella Infection On Trophoblast Functionsmentioning
confidence: 99%